A Classification And Visualization Approach For Knowledge Management Of A Special Interest Group - Sulaiman, Shahida; Ismail, Aisyah; Khader, Ahamad Tajudin; Sabudin, Maziani (2008)
Some Web portals are developed to support electronic community or e-community of special interest groups (SIG) that provide the platforms to communicate, share ideas and knowledge among the members. By incorporating the Web portal with a knowledge-based system, knowledge acquisition and sharing will be more efficient.